Effect of PCM-based cold storage system under periodic and continuous operations on physico-chemical characteristics of mango (Mangifera indica L.) fruit and performance evaluation of mango cold storage systems. Issue 1 (31st December 2022) - Karthikeyan, K.; Mariappan, Vairavan; Sarafoji, P.; Uma Bharathi, K.; Loganathan, M.; Jaya Bharata Reddy, M.; Anish, R.
Abstract : The effects of the PCM-based cold storage system operated under periodic (P12) and continuous (P24) storage conditions on the physico-chemical characteristics of mango fruits were investigated. Fruits in P12 and P24 storage conditions underwent weight loss, peel colour change, soluble solid concentration and maintained high firmness, titratable acidity and ascorbic acid along with the conventional cold storage system (G24). Temperature response and energy consumption revealed that PCM-based cold storage conditions P12 and P24 maintain the temperature within the permissible range and consume less energy than the conventional system. An effective reduction of 39 and 18% of energy consumption was noticed in P12 and P24 PCM-based cold storage conditions. As per these results periodic PCM-based cold storage (P12) can be effectively used as an energy-saving cold storage technology alternative to a conventional cold storage system to maintain the mango fruit quality during power failure and off-peak load conditions.